Zippy – A coarse-grained reconfigurable array with support for hardware virtualization - Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Application-Specific Systems, Architectures, and Processors (ASAP))
This paper motivates the use of hardware virtualization on coarse-grained reconfigurable architectures. We introduce Zippy, a coarse-grained multi-context hybrid CPU with architectural support for efficient hardware virtualization. The architectural details and the corresponding tool flow are outlined. As a case study, we compare the non-virtualized and the virtualized execution of an ADPCM decoder.
Keywords: Zippy